(untitled) (Research, Society and Development, 2022)
Foodborne diseases and microbiological control represent the major challenge for the food industry. New technologies using natural agents have attracted increasing interest. Therefore, this study aimed to evaluate the in vitro susceptibility of Staphylococcus aureus and Escherichia coli to water-soluble curcumin (WSC) combined with acidic pH and blue LED light. The minimum inhibitory concentration (MIC) and bacterial photoinactivation were conducted using different photosensitizer concentrations. For S. aureus, the combination of WSC with lactic acid and 2.5 min illumination time reduced MIC from 500 µg/mL to 15.62 µg/mL, and WSC with citric acid reduced MIC from 125 µg/mL to 7.81 µg/mL after 5 min of light exposure. WSC without illumination did not inhibit E. coli growth (MIC >1,000 µg/mL), however, when applied with photodynamic therapy (5 min blue LED illumination), WSC at 62.5 µg/mL with lactic acid and WSC at 7.81 µg/mL with citric acid eliminated E. coli cells. The results obtained suggest that water-soluble curcumin with organic acids when combined with a blue LED light was effective against foodborne pathogens.